Pathogenesis of Borna Disease Virus: Granulocyte Fractions of Psychiatric Patients Harbor Infectious Virus in the Absence of Antiviral Antibodies - Planz, Oliver (American Society for Microbiology, 1999)
Borna disease virus (BDV) causes acute and persistent infections in various vertebrates. During recent years, BDV-specific serum antibodies, BDV antigen, and BDV-specific nucleic acid were found in humans suffering from psychiatric disorders. Furthermore, viral antigen was detected in human autopsy brain tissue by immunohistochemical staining. Whether BDV infection can be associated with psychiatric disorders is still a matter of debate; no direct evidence has ever been presented. In the present study we report on (i) the detection of BDV-specific nucleic acid in human granulocyte cell fraction from three different psychiatric patients and (ii) the isolation of infectious BDV from these cells obtained from a patient with multiple psychiatric disorders. In leukocyte preparations other than granulocytes, either no BDV RNA was detected or positive PCR results were obtained only if there was at least 20% contamination with granulocytes. Parts of the antigenome of the isolated virus were sequenced, demonstrating the close relationship to the prototype BDV strains (He/80 and strain V) as well as to other human virus sequences. Our data provide strong evidence that cells in the granulocyte fraction represent the major if not the sole cell type harboring BDV-specific nucleic acid in human blood and contain infectious virus. In contrast to most other reports of putative human isolates, where sequences are virtually identical to those of the established laboratory strains, this isolate shows divergence in the region previously defined as variable in BDV from naturally infected animals.